Exploring the Monosodium Glutamate (MSG) and Its Role to Consumption Behaviors Regarding Food Safety - Jebreen, Ali; Khairi, Amalya Nurul (Universitas Ahmad Dahlan, 2025)
This article explores the role of monosodium glutamate (MSG) in food safety by examining recent research findings and regulatory perspectives. MSG, a commonly used flavor enhancer in processed foods, has been the subject of controversy regarding its safety for consumption. The research encompasses studies on MSG consumption and its potential health effects, metabolism in the body, safety for different population groups, and regulatory assessments by agencies like the U.S. Food and Drug Administration (FDA) and the European Food Safety Authority (EFSA). Despite conflicting findings and public perceptions, scientific evidence suggests that MSG is safe for consumption at current levels found in food products. This article emphasizes the importance of consumer education and regulatory measures in ensuring the safe use of MSG. Further research is needed to address lingering concerns and enhance understanding of MSG's role in food safety.